KANDUNGAN KALIUM TANAH DI BAWAH TEGAKAN JATI (Tectona grandis), MAHONI (Swietenia macrophylla), DAN LEGARAN (Alstonia spectabilis R.Br) DI DALAM PETAK UKUR PERMANEN (Studi Kasus di Hutan Pendidikan Wanagama I, Gunungkidul, Yogyakarta) - , ARI ABRIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wanagama I Forest was built as a pilot from rehabilitation of critical land pattern, and also used as an educational land even research for lecturer and students at the forestry faculty of UGM as well as by other institutions. So, at the Educational Forest of Wanagama I need to be made permanent sample plots (PSPs) to know about the increment of plant grow. PSPs is made on site and on different stands in order to represent the condition of the Educational Forest of Wanagama I. one that can be studied in PSPs is potassium content of soil. Potassium is the third most important element after N and P for plant. This study aims to determine potassium levels of soil from the stands of Teak, Legaran, and the Mahogany at educational Forest of Wanagama I. In research, data retrieval was doing at the field and laboratory, while the data retrieval from the field likes height, diameter, and sample of soil for analyzed in laboratory. In the laboratory analyzed potassium content of soil under the stands of teak, legaran, and mahogany with Atomic Absorption Spectrophotometer instrument and data were analyzed descriptively. From observation to potassium levels of soil under the stands of teak, legaran, and mahogany in the educational forest of wanagama I, it included in the criteria is very low at <0.1 me/100gr. Nutrient levels of potassium in each stand is on Teak 0.003 to 0.020 me / 100gr, on mahogany 0,005-0,013 me/100gr, and on legaran 0,020-0,038 me/100gr. This shows the soil at educational forest of wanagama I in the stand of teak, mahogany, and legaran was very lack of nutrient potassium, and also at educational forest of wanagama I needed treatment of potassium fertilization for plants to grow well.